The Caspian Basin: Status Related Disputes, Energy Transit Corridors and Their Implications for the EU Energy Security - Bajrektarević, Anis H.; Posega, Petra (AEI Insights, 2021)
Regions, rich in energy resources, continue to be of crucial interest to our carbon-powered world. Numerous factors summon concern, those such as international legal status, ownership rights, energy routes, transit corridors, state and corporate interests, environmental hazards, and the overall puzzle of energy diplomacy. Additionally, The Caspian is troubled with its specific complexities, some of which we list in our work. These include undefined legal status, territorial disputes, ethnic instabilities and vicinity to other hot spots, such as the turmoil Middle East and the more recently sparked conflict in Ukraine. Influenced by its geography, The Caspian is also of central interest for European energy security, although the supply chain from the region has been traditionally under Russian control. However, for the past decade or so, the EU has become increasingly ambitious in planning Caspian pipelines that exclude Russian territories; the Nabucco Pipeline project has been at the centre of these strategic efforts for a considerable amount of time. The Caspian is therefore also at the crossroads between grand and conflicting energy interests of Russia and Western Europe.